Mechanical properties of NiTi and CuNiTi shape-memory wires used in orthodontic treatment. Part 1: stress-strain tests - Marco Abdo Gravina; Ione Helena Vieira Portella Brunharo; Cristiane Canavarro; Carlos Nelson Elias; Cátia Cardoso Abdo Quintão (Dental Press Editora, 2013)
OBJECTIVE: This research aimed to compare, through traction tests, eight types of superelastic and heat-activated NiTi archwires, by six trade companies (GAC, TP, Ormco, Masel, Morelli and Unitek) to those with addition of copper (CuNiTi 27ºC and 35ºC, Ormco). METHODS: The tests were performed in an EMIC mechanical testing machine, model DL10000, capacity of 10 tons, at the Military Institute of Engineering (IME). RESULTS: The results showed that, generally, heat-activated NiTi archwires presented slighter deactivation loadings in relation to superelastic. Among the archwires that presented deactivation loadings biologically more adequate are the heat-activated by GAC and by Unitek. Among the superelastic NiTi, the CuNiTi 27ºC by Ormco were the ones that presented slighter deactivation loadings, being statistically (ANOVA) similar, to the ones presented by the heat-activated NiTi archwires by Unitek. When compared the CuNiTi 27ºC and 35ºC archwires, it was observed that the 27ºC presented deactivation forces of, nearly, ⅓ of the presented by the 35ºC. CONCLUSION: It was concluded that the CuNiTi 35ºC archwires presented deactivation loadings biologically less favorable in relation to the other heat-activated NiTi archwires, associated to lower percentage of deformation, on the constant baselines of deactivation, showing less adequate mechanical behavior, under traction, in relation to the other archwires.